The chemotherapeutic potential of Terminalia ferdinandiana: Phytochemistry and bioactivity - Mohanty, S.; Cock, Ian E. (Pharmacognosy Reviews, 2012)
Plants contain a myriad of natural compounds which exhibit important bioactive properties. These compounds may provide alternatives to current medications and afford a significant avenue for new drug discovery. Despite this, little information is available in the literature regarding native Australian plants and their potential for medicinal and industrial uses. Recent studies have reported Terminalia ferdinandiana to be an extremely good source of antioxidants. Indeed, T. ferdinandiana has been reported to have ascorbic acid levels per gram of fruit more than 900 times higher than blueberries. T. ferdinandiana also has high levels of a variety of other antioxidants, including phenolic compounds and anthocyanins. Antioxidants have been associated with the prevention of cancer, cardiovascular diseases, and neurological degenerative disorders. They are also linked with antidiabetic bioactivities and have been associated with the reduction of obesity. Antioxidants can directly scavenge free radicals, protecting cells against oxidative stress-related damage to proteins, lipids, and nucleic acids. Therefore, T. ferdinandiana has potential in the treatment of a variety of diseases and disorders and its potential bioactivities warrant further investigation.
Keywords: Australian medicinal plants; antioxidants; gubinge; Kakadu plum; Terminalia ferdinandiana; vitamin C